Shaking Table Tests on Geocell-Based Countermeasures against Pipe Flotation - Nagatani, Taishi; Ikebata, Ruka; Sonoda, Yusuke; Ito, Shuji; Sawada, Yutaka (Indonesian Geotechnical Journal, 2024)
This study investigates the effectiveness of the geocell-based countermeasures against pipe flotation in liquefied ground using shaking table tests. Liquefaction-induced pipe flotation is a significant issue, particularly for agricultural pipelines, which are often installed in areas with high groundwater level. A conventional method, such as using geotextiles combined with gravel, is effective in mitigating this problem. However, the conventional method includes challenges in terms of workability, presenting a need for more efficient solutions. We propose a novel approach that employs geocells to enhance resistance against pipe flotation while potentially reducing labor costs. Geocells, which can be transported in a compact form and expanded on-site, are filled with soil or gravel to form a robust reinforcement around the pipe. This method is expected to offer significant advantages in terms of ease of installation and overall cost-effectiveness. To validate the effectiveness of the proposed method, we conducted shaking table tests using an aluminum pipe buried in saturated sand within a steel container. In this study, four different experimental cases were conducted: an unreinforced case, a case for the conventional geotextile method, and two cases for the geocell reinforcement. For the two cases with geocell reinforcement, the two experimental conditions were varied in the method of fixing the geocells and in the backfill material around the pipe. The results demonstrated that all conventional and geocell-reinforced methods significantly reduced pipe flotation compared to the unreinforced method. Compared to the unreinforced case, the case for the geocell reinforcement reduced pipe flotation by 24.6 times, and the conventional method reduced it by 13.6 times. In conclusion, the proposed method using geocells to prevent pipe flotation in liquefied ground has been confirmed as an effective alternative to the conventional method. This study provides a practical and labor-saving solution for improving the seismic resistance of buried pipelines in earthquake-prone areas.